2017
DOI: 10.1063/1.4985290
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field simulation of counter-current spontaneous imbibition in a fractured heterogeneous porous medium

Abstract: Spontaneous imbibition is well-known to be one of the most effective processes of oil recovery in fractured reservoirs. However, the detailed pore-scale mechanisms of the counter-current imbibition process and the effects of different fluid/rock parameters on this phenomenon have not yet been deeply addressed. This work presents the results of a new pore-level numerical study of counter-current spontaneous imbibition, using coupled Cahn–Hilliard phase field and Navier–Stokes equations, solved by a finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…At the solid surfaces, no-slip boundary condition is imposed by using the half-way bounceback scheme 53 and the desired contact angle is achieved by using the wetting boundary condition proposed by Xu et al 24 , which modifies the direction of the colour gradient ∇ρ N at the boundary to match the specified contact angle θ . These boundary conditions are to maintain a counter-current imbibition environment in which the oil in the matrix can only flow into the fracture that supplies water, which have been widely adopted in the previous numerical and experimental studies of counter-current imbibition 4,9,23,54 . Among various factors that influence the capillary imbibition, surface wettability is of vital importance for both imbibition rate and ultimate oil recovery, and its effect has been thoroughly investigated by Rokhforouz and Amiri 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the solid surfaces, no-slip boundary condition is imposed by using the half-way bounceback scheme 53 and the desired contact angle is achieved by using the wetting boundary condition proposed by Xu et al 24 , which modifies the direction of the colour gradient ∇ρ N at the boundary to match the specified contact angle θ . These boundary conditions are to maintain a counter-current imbibition environment in which the oil in the matrix can only flow into the fracture that supplies water, which have been widely adopted in the previous numerical and experimental studies of counter-current imbibition 4,9,23,54 . Among various factors that influence the capillary imbibition, surface wettability is of vital importance for both imbibition rate and ultimate oil recovery, and its effect has been thoroughly investigated by Rokhforouz and Amiri 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The counter-current imbibition occurs more often although it is less effective in terms of oil recovery. The spontaneous imbibition is known to be affected by many factors including the wettability 4 , the porosity, permeability and heterogeneity of the matrix [5][6][7][8][9][10][11] , the viscosity ratio of the wetting to non-wetting fluids 12,13 and their interfacial tension 14,15 , as well as initial saturation and boundary conditions 10,14,16 , etc. The spontaneous imbibition in conventional porous media has been extensively studied [17][18][19][20] due to its wide existence in various disciplines such as oil recovery, polymer composite manufacturing, soil science and subsurface hydrology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COMSOL Multiphysics [66] software has become a reliable tool for solving two-phase flow problem, which includes interface capturing methods (e.g., phase-field, and level set) [56,61,63,67]. Navier-Stokes equations coupled with a diffuse interface method are available in the microfluidics module of the software.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Numerical studies of governing mechanisms of two-phase flow in porous media have been conducted by many researchers [42,43]. Pore-network modeling [44][45][46], smoothed particles hydrodynamics [47,48], Lattice Boltzmann (LB) [49,50], quasi-static [51,52] and direct numerical simulation approaches based on interface capturing techniques such as Volume of Fluid (VoF) [46,53,54], level set [55] and phase-field [56][57][58][59] are the most common approaches which have been developed to simulate the multiphase flow in porous media. A detailed study of advantages and drawbacks of these techniques can be found elsewhere [60].…”
Section: Introductionmentioning
confidence: 99%